Analysis of the effect of Diet and Physical Activity on the Risk of Non-Communicable Diseases in the community - Dona Suzana; Didik Cahyono; Hayuti Windha Pagiu; Silvia Anita Yuningsih (PT. Anagata Sembagi Education, 2025)
Non-communicable diseases (NCDs) are a significant global health concern, particularly in developing countries, with diet and physical activity identified as key modifiable risk factors. This study aims to analyze the impact of diet and physical activity on the risk of NCDs within a local community. A cross-sectional design was employed, with data collected from 230 adult participants through standardized questionnaires assessing dietary habits and physical activity levels, alongside physical examinations to measure BMI, blood pressure, and other relevant health indicators. The findings indicate that a healthy diet, characterized by balanced nutrition and adequate intake of fruits and vegetables, significantly reduces the risk of NCDs, while regular physical activity further lowers the likelihood of developing conditions such as hypertension, diabetes, and cardiovascular diseases. The combined effect of both factors shows a more pronounced protective effect than either factor alone. The study underscores the importance of lifestyle modifications in preventing NCDs and suggests that community-based interventions promoting healthy eating and physical activity are essential for reducing the burden of these diseases. This research provides valuable data for developing targeted public health policies and interventions at the local level, with implications for improving overall community health outcomes. Future research should explore longitudinal designs to establish causal relationships and further investigate other influencing factors such as stress and genetics.